Knitting Legislative Meaning: A Review of Disability Education Policy in the Law on the National Education System and Disabilities - Zamroni Abdussamad; Anna Triningsih; Mohamad Hidayat Muhtar; Arief Fahmi Lubis; Wiwik Widyo Widjajanti; Dede Agus (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
This study set out to address the question, "How is the future legal construction of the pattern of implementing inclusive, specialized, and equal Education for Persons with Disabilities in Indonesia?" The normative issue of how disabled people in Indonesia are often managed inspired this study. The Law on the Education System and the Law on Disabilities both include ambiguous principles on inclusive and special (segregated) education. The Statute Approach method was used to conduct this normative assessment of the law. The study's findings suggest that moving forward, Indonesia will revise legal norms in both laws and the integration of special schools and regular schools by establishing special units in regular schools to accommodate students with disabilities, all with the goal of achieving full inclusive education for people with disabilities. This may be done in increments, on a continuous basis, and using metrics based on the state of Indonesia's infrastructure right now